2001
DOI: 10.1007/pl00002015
|View full text |Cite
|
Sign up to set email alerts
|

Amlodipin versus Nifedipin retard Eine randomisierte Doppelblindstudie zum Vergleich der Langzeitwirksamkeit und Verträglichkeit von Amlodipin und Nifedipin retard in der Monotherapie der chronisch stabilen Angina pectoris

Abstract: The results of this study show that once daily amlodipine offers comparable antianginal and antiischemic efficacy as twice daily sustained release nifedipine in the monotreatment of chronic stable angina pectoris. Given the lower incidence of adverse events with amlodipine and its convenient once daily dosing regimen, however, amlodipine may help to enhance patient compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have shown that it is better tolerated when compared with other L-type calcium channel blockers like nifedipine. 30 It is also available at an easily affordable price that allows maximum compliance and makes the drug highly suitable for our study. Based on the studies available to date, amlodipine should be initiated in children at a dose of 0.05–0.1 mg/kg/day given once daily.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that it is better tolerated when compared with other L-type calcium channel blockers like nifedipine. 30 It is also available at an easily affordable price that allows maximum compliance and makes the drug highly suitable for our study. Based on the studies available to date, amlodipine should be initiated in children at a dose of 0.05–0.1 mg/kg/day given once daily.…”
Section: Methodsmentioning
confidence: 99%